Digital sustainability, climate change, and information systems solutions: Opportunities for future research. (April 2022) - Pan, Shan L.; Carter, Lemuria; Tim, Yenni; Sandeep, M.S.
Abstract: Climate change is one of the most pressing global challenges facing society today, with potentially detrimental sustainability impacts on individuals, organisations, and societies. The impact of digital technologies on climate change is one of our key research priorities at the Digital Sustainability Knowledge Hub of the University of New South Wales, Australia. Building on digital sustainability research, we call for research contributions to mitigate and adapt to the effects of climate change, as it could cause far-reaching disruptions to communities and the economy here in Australia and worldwide. In this article, we provide an overview of Australia's perspectives and approaches to addressing climate change. Moreover, to encourage researchers to study and develop solutions, we propose future research directions focusing on climate resilience, climate-conscious citizen science, and organisations' Environmental, Social and Governance (ESG) strategies.